Epithelial Cell Gene Expression Induced by Intracellular Staphylococcus aureus. (5th January 2009) - Li, Xianglu; Fusco, William G.; Seo, Keun S.; Bayles, Kenneth W.; Mosley, Erin E.; McGuire, Mark A.; Bohach, Gregory A.
Abstract : HEp-2 cell monolayers were cocultured with intracellular Staphylococcus aureus, and changes in gene expression were profiled using DNA microarrays. Intracellular S. aureus affected genes involved in cellular stress responses, signal transduction, inflammation, apoptosis, fibrosis, and cholesterol biosynthesis. Transcription of stress response and signal transduction-related genes including atf3, sgk, map2k1, map2k3, arhb, and arhe was increased. In addition, elevated transcription of proinflammatory genes was observed for tnfa, il1b, il6, il8, cxcl1, ccl20, cox2, and pai1 . Genes involved in proapoptosis and fibrosis were also affected at transcriptional level by intracellular S. aureus . Notably, intracellular S. aureus induced strong transcriptional down-regulation of several cholesterol biosynthesis genes. These results suggest that epithelial cells respond to intracellular S. aureus by inducing genes affecting immunity and in repairing damage caused by the organism, and are consistent with the possibility that the organism exploits an intracellular environment to subvert host immunity and promote colonization.